Perfil y Tipología del Cuestionario de Eficacia Colectiva para el Deporte (CEQS) en Colombia - Ladrón, Amalia Gissell (2022)
The factorial structure, the psychometric properties and the norms of interpretation and correction of the profile, and the typology of the adaptation to Spanish of the Collective Efficacy Questionnaire for Sport (CEQS) by Martínez, Guillén & Feltz (2011) are examined, in a sample of Colombian athletes, because in their previous validations no strategies were applied to minimize the bias from factorial indeterminacy, confirmatory and by capitalization on the chance. Contrary to the CEQS five-factors structure originally postulated by Martínez et al. (2011), findings in this study show a two-factor structure. Convergent validity shows that the two factors predict the quality of the players' relationship. Finally, no differences were found in the scores of the two CEQS factors associated with sociodemographic or socio-sports variables. Recommendations are presented on the use and interpretation of this instrument by experts in sport psychology, coaches, and sports administrators, and the contribution of the implementation of the CEQS to the improvement of effectiveness in team sports.